Strengthening business capital in the Halal industry through Waqf: ANP analysis of the Waqfpreneur program - Sujono, Rusny Istiqomah (Faculty of Islamic Economics and Business UIN Salatiga, 2024)
This study examines how the Indonesian Waqf Education Foundation's Waqfpreneur program strengthens business capital in the halal industry through the waqf mechanism. The halal industry in Indonesia has experienced significant growth but still faces challenges in terms of financing and business capital. Waqf, as an Islamic financial instrument, offers a potential solution to overcome this problem. The Waqfpreneur program is an innovation in waqf management that aims to support halal industry entrepreneurs by providing business capital through a productive waqf scheme. This study employs the Analytic Network Process (ANP) method, enabling a thorough assessment of multiple factors that impact the program's success. The study's results show that the main benefit of strengthening business capital through waqf is avoiding Riba capital, while the main opportunity is expanding the Indonesian halal industry market. Next, we must consider the cost of waqf management, taking into account the full value of the waqf. In the halal industry, compliance with halal standards poses the main risk.